Semiotic Analysis of Roland Barthes in the Novel the Magic Library: Bibbi Bokken's Magic Library - Noor Arief; Bella Septi Maulidya (Library and Information Science Study Program, Faculty of Humanities, Univ. Diponegoro, 2026)
Background: Libraries and books are not merely physical repositories of information but cultural constructs that reflect how societies perceive, organize, and transmit knowledge. Literary works such as The Magic Library: Bibbi Bokken’s Magic Library offer a meaningful lens through which these cultural meanings can be examined, particularly in understanding libraries as symbolic spaces of knowledge and literacy.Objective: This study aimed to analyze how meanings related to books, libraries, and knowledge are constructed through systems of signs in a literary text using Roland Barthes’ semiotic framework of denotation, connotation, and myth.Methods: This study uses qualitative interpretative approach using Roland Barthes’ textual semiotic analysis method. The research demonstrates that the novel produces a myth in which knowledge gains meaning only through organization and accessibility.Results: The study found The Magic Library: Bibbi Bokken’s Magic Library constructs meaning through librarianship-related symbols that represent knowledge, information order, and cultural continuity. Using Roland Barthes’ semiotic framework, the analysis shows that the library is portrayed not merely as a physical repository of books, but as a living epistemological space that emphasizes the importance of information organization, accessibility, and the sustained development of human knowledge within cultural and ideological contexts.Conclusion: These results indicate that The Magic Library: Bibbi Bokken’s Magic Library portrays the library as more than a fantasy setting, presenting it as a symbol of knowledge, memory, and civilization. Through Barthes’ semiotic framework, the novel emphasizes the importance of systematic information management and the enduring role of libraries as living spaces that connect past, present, and future knowledge